PERAN AKTOR DALAM PROGRAM PENGENTASAN KEMISKINAN BERBASIS EKONOMI RUMAH TANGGA (P2KBERT) DI KECAMATAN POLEWALI. - , Ilham Rasyid ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Implementation of various poverty alleviation programs in Indonesia with a model of venture capital assistance to the target group, leaving problems especially in aid refund process. Still lack of commitment and also the role of implementing the program, facilitators and the target group is suppose to be the cause of a refund did not go smoothly. These problems not only appear on the poverty alleviation program born from the central government policy, but also on poverty reduction programs is a policy of the district/city. As happened in the Poverty Program Based Home Economics ( P2KBERT ) as one of the Polewali Mandar Local Government program. As an illustration based on the Financial Statements Polewali Mandar mention the results of the examination in 2011 found many revolving fund more than two years old are not returned by the recipient.District Polewali specialized in arrears problem can be seen from the report Aid Disbursement and Refund P2KBERT Cooperatives SMEs Year 2012-2013. These problems is interesting to see the role of all stakeholders in the program help resolve the issue refunds P2KBERT. Therefore, this study aimed to determine the role and the interaction between actors in P2KBERT namely bureaucracy, civil society organizations ( LPM ) and the onset of the target group in addressing problems in the aid refund District Polewali. Based on the problems and theoretical framework, this thesis uses descriptive method with qualitative approach. Collection of secondary data in the form of program documents and primary data that is the result of in-depth interviews and field observations to then analyzed qualitatively. The results showed that the actor as part of the program that are directly involved in the process of problem solving installment has a very important role. Due to the various treatment steps undertaken through cooperation and coordination between actors, becomes a critical success installment solving problems. The role of the bureaucracy in dealing with aid refund P2KBERT effective enough to give a solution by rescheduling future grant installments. LPM demonstrated a strong commitment to address the issue refunds through business development assistance to the efforts of group members is problematic. The role of the target group is quite helpful with the process of problem solving installment initiatives involving board members at a meeting to discuss and seek solutions faced by members of the group. However, the implementation of the role of actors such programs are not fully able to cope with problems, especially for members of the installment refund assistance already jammed. This is because the members of the group in question does not have the ability to restore aid funds, plus the absence of appropriate sanctions mechanisms and firm of apparatus implementing the program. While the interaction between actors in the form P2KBERT good cooperation and coordination between the bureaucracy, LPM and target groups in solving problems P2KBERT installments. Forms of interaction between actors also gave rise to a conflict occurs and further complicate efforts P2KBERT aid refund. Keywords : Roles, bureaucracy, LPM, the target group, the interaction